Pengembangan Website Desa Berbasis OpenSID di Desa Pesanggrahan Sebagai Digitalisasi Pelayanan Publik - Zaenul Amri; Muhamad Wisma Apriadi; Amir Bagja; M. Nurul Wathani; Zulkipli (Universitas Hamzanwadi, 2026)
The current development of information technology requires village governments to continuously adapt in providing excellent, effective, and transparent public services to achieve good governance. However, Pesanggrahan Village still faces challenges regarding the limited utilization of information technology, particularly concerning the slow management of population administration data and the restricted means of disseminating information to the wider community. Therefore, this activity aims to develop and implement an OpenSID-based village website as a tangible effort to realize the digitalization of public services at the village level. The implementation method involved systematic stages, including observation and analysis of village needs, installation and configuration of the OpenSID system, input of basic village data, along with technical training and mentoring for village apparatuses to ensure independent system management. The results indicate that the village website has been successfully developed. It currently functions optimally as an official information medium, an integrated administrative data management center, and a digital service support tool that simplifies the duties of village officials while improving information accessibility for residents. In conclusion, implementing the OpenSID-based website provides a practical and sustainable solution to accelerate public service digitalization in Pesanggrahan Village, effectively addressing the challenges of limited resources and local technological infrastructure, thereby fostering village independence in the current digital era